PENDAMPINGAN PENINGKATAN DAN PENGEMBANGAN UMKM PARIWISATA DI DESA SUKAJADI KECAMATAN CARITA STRATEGI PEMBERDAYAAN EKONOMI LOKAL MELALUI INOVASI DAN DIGITALISASI - Rosita Wahyiah, Ita; Saepudin, Eli Apud; Rendiyani, M; Sabrina, Ina (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
This service focuses on improving and developing tourism Micro, Small, and Medium Enterprises (MSMEs) in Sukajadi Village, Carita District. The main objective is to formulate a strategy for local economic empowerment through innovation and digitalisation. The method used includes a qualitative approach with data collection through interviews, observations, and literature studies. The results of the service show that MSMEs in Sukajadi Village have great potential to develop, but still face various obstacles such as lack of access to technology, limited capital, and lack of knowledge about digital marketing. Therefore, the proposed empowerment strategy includes information technology training, increased access to business capital, and digital marketing capacity building. The implementation of this strategy is expected to improve the competitiveness of MSMEs, expand market reach, and ultimately improve the economic welfare of local communities. Innovation and digitalisation are key in strengthening MSMEs and making Sukajadi Village a more attractive and competitive tourist destination.